Analysis of implementation factors in the application of building information modeling (BIM) in construction projects: Enhancing disaster preparedness - Lathifia Qolbina; Beatrix, Michella (Calamity: A Journal of Disaster Technology and Engineering, 2025)
Background: Building Information Modeling (BIM) technology is game-changing in the AEC industry. BIM can significantly improve team coordination, construction productivity, project performance, and profits. The conventional construction process, where there are often conflicts between stakeholders regarding the workflow in a job, will change with the application of BIM in construction projects. In the construction sector in Indonesia, the knowledge and experience of construction service provider companies (consultants and contractors) in Indonesia needs to be studied and documented academically to enrich the body of knowledge of BIM implementation. Methods: The data used in this study are primary data obtained through questionnaires.  The data used in this study are quantitative data processed using the Partial Least Square (PLS) method with SmartPLS 4.0 software. Conclusion: From the results of this study, it is concluded that the implementation factor has a significant influence on Building Information Modeling (BIM). Based on the outer model analysis of the SmartPLS 4.0 software, it is found that the greatest influence of the implementation factor relationship on Building Information Modeling (BIM) is 0.757 or it can be said that it is 75.7%. Novelty/Originality of this article: This study provides a unique contribution by focusing on the implementation of Building Information Modeling (BIM) in the Indonesian construction sector, particularly through the lens of construction service providers' knowledge and experience, using a robust quantitative approach with SmartPLS 4.0 to analyze the influence of implementation factors on BIM adoption.